An investigation into whether Curtin University’s Go Global program increases employability: Perceptions of Go Global graduates and teaching staff - Tomlinson, Kristy (Curtin University, 2015)
Australian Universities are placing more emphasis on international fieldwork to develop graduates suitable for the global environment. In this study, Health Science academic staff and graduates identified that important graduate attributes were developed through international fieldwork including: intercultural understanding, interprofessional practice capabilities and the ability to navigate varying social contexts. Data was collected using the Graduate Employability Indicators (Oliver, 2011) and a focus group; results clearly indicated that the international fieldwork experience enhanced graduate employability.